Engineering biomimetic hair bundle sensors for underwater sensing applications - Kottapalli, Ajay Giri Prakash (2018)
We present the fabrication of an artificial MEMS hair bundle sensor designed to approximate the structural and functional principles of the flow-sensing bundles found in fish neuromast hair cells. The sensor consists of micro-pillars of graded height connected with piezoelectric nanofiber “tip-links” and encapsulated by a hydrogel cupula-like structure. Fluid drag force actuates the hydrogel cupula and deflects the micro-pillar bundle, stretching the nanofibers and generating electric charges. These biomimetic sensors achieve an ultrahigh sensitivity of 0.286 mV/(mm/s) and an extremely low threshold detection limit of 8.24 µm/s. A complete version of this paper has been published [1].